EFFECT OF MICROWAVE IRRADIATION TIME TO DEACETYLATION PROCESS OF CHITIN FROM SHRIMP SHELLS - Arief Adhiksana; Wahyudi Wahyudi; Zainal Arifin; Muh Irwan (Jurnal Kimia Riset, 2023)
Microwaves have been used in various organic synthesis applications. The use of microwaves provides many advantages, including relatively short start-up and heating times, energy efficiency and process costs, easy and precise process control, selective heating, better final product quality, and improved dry material quality. Microwaves were used in this study to convert chitin into chitosan and to determine the effect of deacetylation time on the degree of deacetylation of chitosan, which was in accordance with the Indonesian National Standard (SNI 7949:2013). The chitin deacetylation process was carried out by varying the heating time to 5, 7, 11, and 15 minutes with a power of 350 W. Two grams of chitin were mixed with 40 mL of 70% NaOH solution in a beaker. The mixture was put in a microwave at a constant temperature of 70 °C. Chitosan was washed until neutral and then dried in an oven. The degree of deacetylation (DD) was analyzed using Fourier Transform Infrared (FTIR) spectroscopy. The results showed that A deacetylation degree of 79.96% was achieved at a reaction time of 15 min. The water content of chitosan was determined to be 9.15%.